Interorganisational Partnerships And Knowledge Sharing: The Perspective Of Non-Profit Organisations (NPOs). Issue 5 (19th August 2014) - Rathi, Dinesh; Given, Lisa M; Forcier, Eric
Abstract : Purpose: This paper seeks first to identify key interorganisational partnership types among non-profit organisations (NPOs), and secondly to determine how knowledge sharing takes place within each type of partnership. Results explore the value of social media specifically in facilitating external relationships between NPOs, firms and the communities they serve. Design/methodology/approach: Empirical qualitative analysis of exploratory interviews with 16 Canadian NPOs generates a non-exhaustive classification of partnership types emerging from these organisations, and their defining characteristics in the context of interorganisational knowledge sharing. Findings: Findings: Overall eight categories of partnerships from the sampled NPOs emerged from the analysis of the data. These include: business partnerships, sector partnerships, community partnerships, government partnerships, expert partnerships, endorsement partnerships, charter partnerships and hybrid partnerships. Using examples from interviews, the sharing of knowledge within each of these partnerships are defined uniquely in terms of directionality (i.e., uni-directional, bi-directional, multi-directional knowledge sharing) and formality (i.e. informal, semi-formal or formal knowledge sharing).Specific practices within these relationships also arise from examples, in particular the use of social media to support informal and community-driven collaborations. Twitter, as a popular social networking tool, emerges as a preferred medium that supports interorganisational partnerships relevant to NPOs. Originality/value: This research is valuable in identifying the knowledge management practices unique to non-profit organisations. By examining and discussing specific examples of partnerships encountered among NPOs, this paper contributes original findings about the implications of interorganisational knowledge sharing, as well as the impact of emerging social technologies on same.